Estrutura fina do espermatozóide de Acestrorhynchus falcatus Bloch (Teleostei, Characidae) da região norte do Brasil - MATOS, Edilson Rodrigues (2014)
Spermatozoa of amazon fish, Acestrorhynchus falcatus Bloch, 1794 were investigated by optical microscopy (DIC) and electron microscopy (TEM). Spermatozoa have no acrosome, the head is ovoid, and the midpiece region cylindrical, contains spherical mitochondria. The centriolar complex is located at the lateral side of the nucleus, formed by nine peripheral pairs of microtubules and arranged in a right angle to each other. The flagellum consists of nine pairs of peripheral and two central microtubules.